2019
DOI: 10.1590/1982-0275201936e160079
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do coping da dor em crianças com Anemia Falciforme

Abstract: Resumo O enfrentamento (coping) da dor desempenha um papel importante na adaptação à doença crônica e seus efeitos. Este estudo analisou o coping da Anemia Falciforme em 12 crianças com idade entre oito e dez anos, que frequentavam um Hospital Universitário de Vitória, Espírito Santo, pelo Instrumento Informatizado de Avaliação do Enfrentamento da Hospitalização e da Dor. Os resultados mostram que as estratégias de enfrentamento mais frequentes foram ruminação, solução de problemas e reestruturação cognitiva. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
1
0
11
Order By: Relevance
“…The present study identified that children with cancer, in order to adapt to chemotherapy, reported resorting to behaviors with greater chances of an adaptive outcome (Motta et al, 2015) and common in children with chronic diseases and/or hospitalized: watching TV, talking and taking medicines (Caprini & Motta, 2017;Carnier et al, 2015;Garioli et al, 2019;Hostert et al, 2015;Motta et al, 2015;Rocha et al, 2015;Silveira, Lima, & Paula, 2018;Zimmer-Gembeck & Skinner, 2011). However, confirming the literature (Carnier et al, 2015;Kristensen, Schaefer, & Busnello, 2010;Motta et al, 2015;Zimmer-Gembeck & Skinner, 2011), some specificities were observed and associated with sex, age, and type of cancer.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study identified that children with cancer, in order to adapt to chemotherapy, reported resorting to behaviors with greater chances of an adaptive outcome (Motta et al, 2015) and common in children with chronic diseases and/or hospitalized: watching TV, talking and taking medicines (Caprini & Motta, 2017;Carnier et al, 2015;Garioli et al, 2019;Hostert et al, 2015;Motta et al, 2015;Rocha et al, 2015;Silveira, Lima, & Paula, 2018;Zimmer-Gembeck & Skinner, 2011). However, confirming the literature (Carnier et al, 2015;Kristensen, Schaefer, & Busnello, 2010;Motta et al, 2015;Zimmer-Gembeck & Skinner, 2011), some specificities were observed and associated with sex, age, and type of cancer.…”
Section: Discussionsupporting
confidence: 81%
“…These are: self-confidence, search for support, problem solving, search for information, adjustment/adaptation, negotiation, delegation, social isolation, helplessness, avoidance, submission, and opposition (Ramos et al, 2015;Vasconcelos & Nascimento, 2016;Zimmer-Gembeck & Skinner, 2011). This theoretical model was used in several Brazilian studies with sick or hospitalized children, including some with cancer (Caprini & Motta, 2017;Carnier, Padovani, Perosa, & Rodrigues, 2015;Garioli, Paula, & Enumo, 2019;Hostert, Motta, & Enumo, 2015;Oliveira, Enumo, & Paula, 2017;Pagung, Canal, Missawa, & Motta, 2017). In general, the children in these studies reported the use of behaviors with a greater chance of a positive outcome in the adaptive process, such as: taking medicines, talking, watching television, and playing.…”
mentioning
confidence: 99%
“…Assim, o cuidador se utiliza de um conformismo frente à situação, reconhecendo a complexidade e desenvolvendo uma percepção peculiar em relação à doença 20 . A família busca aprender a conviver com a doença e com suas particularidades, enfrentar os momentos de crise e adaptar-se a essa nova situação, na tentativa de manter o equilíbrio no ambiente familiar, necessitando de uma rede de apoio social e institucional, na qual possa encontrar suporte 21 .…”
Section: Resultsunclassified
“…Essa situação faz com que o organismo não receba a quantidade necessária de oxigênio para o pleno desenvolvimento de suas funções, o que contribui para a elevada taxa de mortalidade dos portadores (5,6). Constata-se que, em média, nascem 3.500 pessoas com a anemia falciforme por ano, das quais 20% não chegam a completar cinco anos de idade, conforme dados do Ministério da Saúde brasileiro (7).…”
Section: Doença Falciformeunclassified
“…Como consequência da baixa oxigenação, as hemácias agrupam-se no vaso sanguíneo e impossibilitam o devido fluxo de sangue; assim, ocasionam as manifestações mais frequentes, como: (i) fortes dores ósseas, que, além de permanecerem por dias, são a principal causa de morbidade entre os doentes; (ii) infecções e viroses; (iii) surgimento repentino de graves anemias ferroprivas; (iv) inchaço das mãos e dos pés (síndrome mão-pé); (v) acidentes vasculares cerebrais; (vi) icterícia; (vii) pneumonia; (viii) ulcerações e (ix) aplasia medular (6). Conviver com tais sintomas afeta diretamente a qualidade de vida desses indivíduos, motivo pelo qual a depressão, a ansiedade e o estresse são fatores recorrentes entre os pacientes (7).…”
Section: Doença Falciformeunclassified